ANALISIS HUKUM TERHADAP FUNGSI SUPERVISI OLEH KOMISI PEMBERANTASAN KORUPSI DALAM PENEGAKAN HUKUM DI INDONESIA - Restu, Teguh Amandia; Artina, Dessy; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Substantially, there is a common operational responsibility in terms of carrying out legal actions of investigation and prosecution of corruption perpetrators between the Corruption Eradication Commission and Police investigators. Weak Coordination and Supervision between lines of law enforcement, as well as problems in the implementation of duties and authority, making it possible to have blemishes and lack of accountability or lack of accountability as well as clarity in carrying out duties and authorities in eradicating criminal acts of corruption. This study aims to determine the function of Supervision by the Corruption Eradication Commission in law enforcement in Indonesia and to find out the ideal arrangement of the Supervision function in resolving cases of Corruption in Indonesia. This type of research used in this study is normative legal research. In this normative legal research, the writer conducts a research on law synchronization which starts from the existing law, by conducting an identification in advance of the legal principles that have been formulated in the legislation. The method used by the author in this research is through document study literature study, the type of research data are primary, secondary and tesier legal materials. Data Collection Techniques use normative legal research techniques (legal research) methods used are literature study or documentary studies. Literature study is a data collection technique by conducting a study of books, literature, notes and cases that occur based on the above problems. The task of supervision of the Corruption Eradication Commission has the authority to conduct supervision, research, or study of agencies that carry out their duties and authority relating to the Eradication of Corruption. Supervision is grouped into two types, namely general supervision and special supervision. General supervision of the Police and Attorney General is carried out simultaneously with the time of implementation of coordination. Whereas special supervision of cases handled by the prosecutor and the police is carried out at the request of the police or the prosecutor's office or at the initiative of the KPK based on the KPK leadership's consideration. Keywords: Criminal Action, Corruption, Supervision Function, Corruption Eradication Commission.